Sleeping Beauty - "Grimm, Brothers" (MM publications, 2008)
Sleeping Beauty is a classic fairy tale about a princess who falls into a deep, enchanted sleep after pricking her finger on a spindle, only to be awakened by a prince's kiss. The story explores themes of fate, magic, and the triumph of good over evil. The earliest known version appears in Giambattista Basile s 1634 Sun, Moon, and Talia, followed by Charles Perrault s La Belle au Bois Dormant (1697), which introduced elements such as the fairy godmothers. The Brothers Grimm later adapted it as Dornröschen (1812), solidifying its place in European folklore.
Keywords: Classic Fairy Tale